The Use of Multimedia Education in Cancer Patient Management: A Literatur Review - Sandrelly, Riga Opri; Huda, Nurul; Erika, Erika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer develops a variety of complex difficulties, both physically and psychologically. Providing educational interventions to cancer patients has proven to be beneficial. Objective: this literature review aimed to determine how multimedia education is employed and the benefits of multimedia education interventions in cancer patients. Method: the literature search was conducted using the electronic databases ScienceDirect, Scopus, Proquest, and Clinicalkey. The keywords used in the article search were 'cancer' and 'multimedia education'. The inclusion criteria for this study were quantitative with an experimental design and quasi-experimental. Other inclusion criteria were published in English between 2015 and 2024. Results: From the 1056 articles found, 7 articles were analyzed revealed that cancer patients were offered various types of multimedia in the form of text, video, audio, or animation. Using multimedia-based interventions can promote disease knowledge, understanding, and acceptance, hence improving quality of life and treatment compliance. Conclusions: this literature review concludes that multimedia-based interventions have a greater favorable impact on cancer patients than conventional education. Therefore, medical personnel, particularly nurses, can provide multimedia-based educational interventions to cancer patients.